2015
DOI: 10.1093/molbev/msv113
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Chromosome Homomorphy in Palearctic Tree Frogs Results from Both Turnovers and X–Y Recombination

Abstract: Contrasting with birds and mammals, poikilothermic vertebrates often have homomorphic sex chromosomes, possibly resulting from high rates of sex-chromosome turnovers and/or occasional X-Y recombination. Strong support for the latter mechanism was provided by four species of European tree frogs, which inherited from a common ancestor (∼ 5 Ma) the same pair of homomorphic sex chromosomes (linkage group 1, LG1), harboring the candidate sex-determining gene Dmrt1. Here, we test sex linkage of LG1 across six additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 55 publications
4
84
0
Order By: Relevance
“…However, in the European tree frog group ( H. arborea, H. intermedia, and H. molleri ), it was observed that the sex chromosomes did not experience any turnover for a long time (5 MY), although they remain homomorphic in both sexes [Dufresnes et al, 2015]. In contrast, sex chromosomes turned over between geographic populations within a single species of the Japanese, European, and North American frog species mentioned earlier.…”
Section: Why Turnovers?mentioning
confidence: 91%
“…However, in the European tree frog group ( H. arborea, H. intermedia, and H. molleri ), it was observed that the sex chromosomes did not experience any turnover for a long time (5 MY), although they remain homomorphic in both sexes [Dufresnes et al, 2015]. In contrast, sex chromosomes turned over between geographic populations within a single species of the Japanese, European, and North American frog species mentioned earlier.…”
Section: Why Turnovers?mentioning
confidence: 91%
“…For nuclear data, we amplified and cloned a ~500 bp part α-Fibrinogen intron 1 (methods and cross-amplifying primers: [29]) in a representative subset of individuals ( H. japonica : n  = 36, H. immaculata : n  = 2; we included published sequences for H. suweonensis , see below). At least eight clones were sequenced per sample in order to capture the two alleles of heterozygotes.…”
Section: Methodsmentioning
confidence: 99%
“…Homomorphy may result from occasional X-Y recombination and/or frequent sex-chromosome turnovers (see, for example, Stöck et al, 2011;Dufresnes et al, 2015), two mechanisms possibly driven by incomplete genetic control over sex determination (Perrin, 2009;Grossen et al, 2011). Sexdetermination systems seem particularly labile in Ranidae, where sex chromosomes may differ between closely related species or even conspecific populations (Nishioka and Sumida, 1994;Miura, 2007).…”
Section: Introductionmentioning
confidence: 99%